Cloud based manufacturing: A review of recent developments in architectures, technologies, infrastructures, platforms and associated challenges - Gharibvand, Vahid; Kolamroudi, Mohammad Karimzadeh; Zeeshan, Qasim; Cinar, Zeki Murat; Sahmani, Saeid; Asmael, Mohammed; Safaei, Babak (Springer London Ltd, 2024)
Service-provider industries have used cloud-based technologies in recent years. Information technology (IT) led the development of electronic hardware and software technologies to enable cloud computing as a new paradigm. Other vanguard industries such as communications and financial services leveraged cloud computing technology to develop cloud-based platforms for their respective industries. Manufacturing industry is a relative newcomer to cloud technologies although it has used modern technologies on factory floor to boost production efficiency. Cloud manufacturing (CMfg) is one of the key technologies of Industry 4.0 (I 4.0) and the goal of CMfg is to develop cloud-based approaches in manufacturing that provide flexibility, adaptability, and agility also, reduces challenges caused by system complexity. In recent years, researchers evaluated cloud technologies and proposed initial solutions tailored to manufacturing requirements. However, there are challenges in implementing CMfg due to complexity of technologies, different types of products and wide range of requirements from mass production of consumer products to low-volume specialty products. This paper presents the advantages, challenges and shortcomings associated with applications of the latest technologies to drive transition to CMfg. This research examined cloud technologies proposed for implementation of CMfg such as architectures, models, frameworks, infrastructure, interoperability, virtualization, optimal service selection, etc. This research also studied the role of technologies such as the internet of things (IoT), cyber physical systems (CPS) robotics, big data, radio frequency identification (RFID), 3D printing and artificial intelligence (AI) in accelerating the adoption and future direction of CMfg.
Keywords: Cloud computing; Cloud technologies; Cloud manufacturing; Intelligent manufacturing